Penatalaksanaan Holistik dengan Pendekatan Dokter Keluarga pada Wanita Usia 42 Tahun dengan Asma Persisten Sedang - Annisa, Nur; Karyus, Aila (Medula, 2025)
Asthma is a heterogeneous disease, which has characteristics of chronic inflammation of the airways characterized by a history of respiratory symptoms such as wheezing, shortness of breath, chest tightness, and coughing that vary in terms of time and intensity, accompanied by variations in expiratory airflow obstruction. This study is a descriptive study of case reports. Primary data were obtained through autoanamnesis, physical examination, and visits to the patient's home. Secondary data were obtained from patient medical records at Panjang Public Health Center. Patient Mrs. LM, 42 years old, diagnosed with moderate persistent Asthma was managed comprehensively, namely given medication in the form of bronchodilators and inhalers and carried out interventions using poster media and showing asthma exercise videos. The evaluation obtained results in the form of improved patient complaints, increased understanding of the disease as evidenced by a comparison of pre-test and post-test values and increased family support The application of a family doctor approach is needed for holistic and comprehensive management of patients with moderate persistent Asthma to detect internal and external risk factors in order to support successful therapy and improve the patient's quality of life.